Use of a Cryptic Splice Site for the Expression of Huntingtin Interacting Protein 1 in Select Normal and Neoplastic Tissues - Graves, Chiron W. (2008)
Huntingtin interacting protein 1 (HIP1) is a 116-kDa endocytic protein, which is necessary for the maintenance of several tissues in vivo as its deficiency leads to degenerative adult phenotypes. HIP1 deficiency also inhibits prostate tumor progression in mice. To better understand how deficiency of HIP1 leads to such phenotypes, we analyzed tumorigenic potential in mice homozygous for a Hip1 mutant allele, designated Hip1(Δ3-5), which is predicted to result in a frame-shifted, nonsense mutation in the NH(2) terminus of HIP1. In contrast to our previous studies using the Hip1 null allele, an inhibition of tumorigenesis was not observed as a result of the homozygosity of the nonsense Δ3-5 allele. To further examine the contrasting results from the prior Hip1 mutant mice, we cultured tumor cells from homozygous Δ3-5 allele–bearing mice and discovered the presence of a 110-kDa form of HIP1 in tumor cells. Upon sequencing of Hip1 DNA and message from these tumors, we determined that this 110-kDa form of HIP1 is the product of splicing of a cryptic U12-type AT-AC intron. This event results in the insertion of an AG dinucleotide between exons 2 and 6 and restoration of the reading frame. Remarkably, this mutant protein retains its capacity to bind lipids, clathrin, AP2, and epidermal growth factor receptor providing a possible explanation for why tumorigenesis was not altered after this knockout mutation. Our data show how knowledge of the transcript that is produced by a knockout allele can lead to discovery of novel types of molecular compensation at the level of splicing.